Jack’s Milyader: Manajemen Keuangan untuk Remaja Melalui Literasi Keuangan di Kalangan Siswa SMA Negeri 1 Berastagi - Anita Tarihoran; Yola Yolanda; Purnaya Sari Tarigan; Suci Pertiwi (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
The increasingly complex development of the global economy requires every individual to have knowledge and skills in managing personal finances. Instilling financial literacy from an early age is crucial, particularly during adolescence when mindsets and habits are forming. In Indonesia, the level of financial literacy is still relatively low, especially among teenagers. Based on a survey by the Financial Services Authority (OJK) in 2024, the level of financial literacy among the Indonesian people only reached 65.43%, far below that of developed countries, which reached 70–80%. SMA Negeri 1 Berastagi, as one of the upper secondary education institutions in Karo Regency, North Sumatra, has great potential to become a pioneer in developing financial literacy among teenagers. With more than 1,000 students coming from various socio-economic backgrounds, this school is an ideal place to instill and develop personal financial management skills. The service team conducted a needs survey directly with the principal of SMA Negeri 1 Berastagi, and the results of the discussion showed that students had not received financial literacy insights and there was no direction that educated them to have intelligence in financial management for their better future. The results of the service of SMA Negeri 1 Berastagi are that students understand financial management for adolescents through financial literacy.